Essays on oil and business cycles in Saudi Arabia - Aba Alkhail, Bandar A. (Kansas State University, 2007)
This dissertation consists of three chapters. Chapter one presents a theoretical model using a dynamic stochastic general equilibrium (DSGE) approach to investigate the role of world oil prices in explaining the business cycle in Saudi Arabia. This model incorporates both productivity and oil revenue shocks. The results indicate that productivity shocks are relatively more important to business cycles than oil shocks. However, this model has some unfavorable features that are associated with both investment and labor hours. The second chapter presents a modified theoretical model using DSGE approach to examine the role of world oil prices versus productivity shocks in explaining the business cycles in Saudi Arabia. To overcome the unfavorable features of the baseline model, the alternative model adds friction to the model by incorporating investment portfolio adjustment. Thus, the alternative model produces similar dynamics to that of the baseline model but the unfavorable characteristics are eliminated. Also, this chapter conducts sensitivity analysis. The objective of the third chapter is to empirically investigate how real world oil price and productivity shocks affect output, consumption, investment, labor hours, and trade balance/output ratio for Saudi Arabia. This chapter complements the theoretical model of the previous chapters. In addition, this study builds a foundation for future studies in examining the impact of real world oil price shocks on the economies of key trade partners of Saudi Arabia. The results of the third chapter show that productivity shocks matter more for macroeconomic fluctuations than oil shocks for the Saudis’ primary trade partners. Therefore, fears of oil importing countries appear to be overstated. As a whole, this research is important for the following reasons. First, the empirical model is consistent with the predictions of our theoretical model in that productivity is a driving force of business cycles in Saudi Arabia. Second, the policymakers in Saudi Arabia should be more concerned with increasing productivity through adopting new technologies that increase economic prosperity. Therefore, the policymakers should continue diversifying economic resources and reduce their reliance on oil.
Keywords: Saudi Arabia; economics; Economics, General (0501)